TESTING RELIABILITY OF SERUM SAMPLES AS A DNA SOURCE ON CAPTIVE BREEDING LONG-TAILED MACAQUES (Macaca fascicularis) - Dyah Perwitasari-Farajallah; Achmad Farajallah (BIOTROPIA, 2014)
The serum realibility was tested in captive breeding conditions on the long-tailed macaques (Macaca fascicularis). Serum and buffy coat were applied to standard protocol of DNA extration following the amplification of microsatellite DNA locus of D2S1777 by PCR and visualized PCR products by means of PAGE with silver staining.Â  The amount of genomic DNA extracted from serum was sufficient for genotyping individuals at DNA microsatellite locus of D2S1777 with the allele size is approximately 160 bp.Â  We show that serum can provide a reliable alternative for obtaining DNA where taking blood using anticoagulant is impracticable